The brain's supply and demand in obesity - Kubera, Britta; Hubold, Christian; Zug, Sophia; Wischnath, Hannah; Wilhelm, Ines; Hallschmid, Manfred; Entringer, Sonja; Langemann, Dirk; Peters, Achim (Frontiers in Neuroenergetics, 2012)
During psychosocial stress, the brain demands extra energy from the body to satisfy its increased needs. For that purpose it uses a mechanism referred to as “cerebral insulin suppression” (CIS). Specifically, activation of the stress system suppresses insulin secretion from pancreatic beta-cells, and in this way energy – particularly glucose – is allocated to the brain rather than the periphery. It is unknown, however, how the brain of obese humans organizes its supply and demand during psychosocial stress. To answer this question, we examined 20 obese and 20 normal weight men in two sessions (Trier Social Stress Test and non-stress control condition followed by either a rich buffet or a meager salad). Blood samples were continuously taken and subjects rated their vigilance and mood by standard questionnaires. First, we found a low reactive stress system in obesity. While obese subjects showed a marked hormonal response to the psychosocial challenge, the cortisol response to the subsequent meal was absent. Whereas the brains of normal weight subjects demanded for extra energy from the body by using CIS, CIS was not detectable in obese subjects. Our findings suggest that the absence of CIS in obese subjects is due to the absence of their meal-related cortisol peak. Second, normal weight men were high reactive during psychosocial stress in changing their vigilance, thereby increasing their cerebral energy need, whereas obese men were low reactive in this respect. Third, normal weight subjects preferred carbohydrates after stress to supply their brain, while obese men preferred fat and protein instead. We conclude that the brain of obese people organizes its need, supply and demand in a low reactive manner.